Detection and characterization of a novel bat-borne coronavirus in Singapore using multiple molecular approaches. (16th August 2019) - Lim, Xiao Fang; Lee, Chengfa Benjamin; Pascoe, Sarah Marie; How, Choon Beng; Chan, Sharon; Tan, Jun Hao; Yang, Xinglou; Zhou, Peng; Shi, Zhengli; Sessions, October M.; Wang, Lin-Fa; Ng, Lee Ching; et al.
Abstract : Bats are important reservoirs and vectors in the transmission of emerging infectious diseases. Many highly pathogenic viruses such as SARS-CoV and rabies-related lyssaviruses have crossed species barriers to infect humans and other animals. In this study we monitored the major roost sites of bats in Singapore, and performed surveillance for zoonotic pathogens in these bats. Screening of guano samples collected during the survey uncovered a bat coronavirus ( Betacoronavirus ) in Cynopterus brachyotis, commonly known as the lesser dog-faced fruit bat. Using a capture-enrichment sequencing platform, the full-length genome of the bat CoV was sequenced and found to be closely related to the bat coronavirus HKU9 species found in Leschenault's rousette discovered in the Guangdong and Yunnan provinces.